Natural nitric oxide (NO) inhibitors from the rhizomes of Curcuma phaeocaulis1. Issue 30 (14th August 2015) - Ma, Jiang-Hao; Zhao, Feng; Wang, Ying; Liu, Yue; Gao, Su-Yu; Ding, Li-Qin; Chen, Li-Xia; Qiu, Feng
<x xml:space="preserve">Abstract</x> Four new sesquiterpenes, two nor-sesquiterpenes including a new skeleton, one cyclic diarylheptanoid, and one aromatic acid were isolated from Curcuma phaeocaulis.